Can the heart rate response at the respiratory compensation point be used to retrieve the maximal metabolic steady state? - Iannetta, D.; Marinari, G.; Murias, J. M. (Journal of Sports Sciences, 2023)
The metabolic rate (VO2) at the maximal metabolic steady state (MMSS) is generally not different from the VO2 at the respiratory compensation point (RCP). Based on this, it is often assumed that the heart rate (HR) at RCP would also be similar to that at MMSS. The study aims to compare the HR at RCP with that at MMSS. Seventeen individuals completed a ramp-incremental test, a series of severe-intensity trials to estimate critical power and two-to-three 30-min trials to confirm MMSS. The HR at RCP was retrieved by linear interpolation of the ramp-VO2/HR relationship and compared to the HR at MMSS recorded at 10, 15, 20, 25 and 30 min. The HR at RCP was 166 ± 12 bpm. The HR during MMSS at the timepoints of interest was 168 ± 8, 171 ± 8, 175 ± 9, 177 ± 9 and 178 ± 10 bpm. The HR at RCP was not different from the HR at MMSS at 10 min (P > 0.05) but lower at subsequent timepoints (P < 0.05) with this difference becoming progressively larger. For all timepoints, limits of agreement were large (~30 bpm). Given these differences and the variability at the individual level, the HR at RCP cannot be used to control the metabolic stimulus of endurance exercise.